(x+y)三次方乘以(x-y)减(x+y)(x-y)三次方(x+y)三次方乘以(x-y)减(x+y)(x-y)三次方因式分解

(x+y)三次方乘以(x-y)减(x+y)(x-y)三次方(x+y)三次方乘以(x-y)减(x+y)(x-y)三次方因式分解(x+y)三次方乘以(x-y)减(x+y)(x-y)三次方(x+y)三次方乘

(x+y)三次方乘以(x-y)减(x+y)(x-y)三次方(x+y)三次方乘以(x-y)减(x+y)(x-y)三次方因式分解
(x+y)三次方乘以(x-y)减(x+y)(x-y)三次方
(x+y)三次方乘以(x-y)减(x+y)(x-y)三次方
因式分解

(x+y)三次方乘以(x-y)减(x+y)(x-y)三次方(x+y)三次方乘以(x-y)减(x+y)(x-y)三次方因式分解
原式=(x+y)^3(x-y)-(x+y)(x-y)^3
=(x+y)(x-y)[(x+y)^2-(x-y)^2]
=(x+y)(x-y)[x^2+2xy+y^2-x^2+2xy-y^2]
=4xy(x+y)(x-y)

(x+y)^3(x-y)-(x+y)(x-y)^3=4xy(x+y)(x-y)

(x+y)^3(x-y)-(x+y)(x-y)^3
=(x+y)(x-y)((x+y)^2-(x-y)^2)
=4(x^2-y^2)xy
=4x^3y-4xy^3